Gaussian basis sets by generator coordinate Hartree-Fock method to ab initio calculations of electron affinities of enolates - Savedra, RML; Pinheiro, J. C.; Treu, O.; Kondo, R. T. (Elsevier B.V., 2002)
The Generator Coordinate Hartree-Fock (GCHF) method is employed to generate uncontracted 15s and 18s11p gaussian basis sets for the H, C and O atoms, respectively. These basis sets are then contracted to 3s and 4s H atom and 6s5p, for C and O atoms by a standard procedure. For quality evaluation of contracted basis sets in molecular calculations, we have accomplished calculations of total and orbital energies in the Hartree-Fock-Roothaaii (HFR) approach for CH, C(2) and CO molecules. The results obtained with the uncontracted basis sets are compared with values obtained with the standard D95, 6-311G basis sets and with values reported in the literature. The 4s and 6s5p basis sets are enriched with polarization and diffuse functions for atoms of the parent neutral systems and of the enolates anions (cycloheptanone enolate, 2,5-dimethyleyelopentanone enolate, 4-heptanone enolate, and di-isopropyl ketone enolate) from the literature, in order to assess their performance in ab initio molecular calculations, and applied for calculations of electron affinities of the enolates. The calculations were performed at the DFT (BLYP and B3LYP) and HF levels and compared with the corresponding experimental values and with those obtained by using other 6-3 1 + +G((*)) and 6-311 + +G((*)) basis sets from literature. For the enolates studied, the differences between the electron affinities obtained with GCHF basis sets, at the B3LYP level, and the experimental values are -0.001, -0,014, -0.001, and -0.001 eV. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: Gaussian basis sets; GCHFM; electron affinities; calculations of enolates; electron affinities of enolates